A CM-DEMATEL assessment of SME competitiveness factors - Bastos, X.; Ferreira, F.; Kannan, D.; Ferreira, N.; Banaitienė, N. (CIRP Journal of Manufacturing Science and Technology, 2023)
Competitiveness is a crucial dimension in accurate assessments of organizations’ use of their resources and capabilities, which, if utilized effectively and efficiently, allow companies to achieve numerous competitive advantages. Firm level of competitiveness has assumed increasing importance, especially for small and medium-sized enterprises (SMEs), as it generates not only better organizational performance but also, in many cases, business activity survival. However, assessing competitiveness factors (CFs) is a complex, challenging endeavor given the multiple variables that influence companies’ competitiveness. Thus, a comprehensive evaluation model is a necessary tool for decision makers who seek to assess their organization’s competitiveness. To overcome previous research limitations, this study combines cognitive mapping and the decision-making trial and evaluation laboratory (DEMATEL) method to develop a complete, well-informed model that facilitates dynamic analyses of cause-and-effect relationships among CFs. Two in-person sessions were held with a panel of specialists in SME competitiveness, during which five clusters of CFs emerged from the discussion and knowledge shared. The results were subsequently validated by a neutral expert. The advantages and limitations of the proposed framework are also analyzed.